The Road to the Baccalaureate: Assessing the Viability of Community Colleges as Transfer Pathways for International Students - Ghazzawi, Dina; McKinney, Lyle; Horn, Catherine Lynn; Carales, Vincent; Burridge, Andrea (Journal of International Students, 2020)
International students are increasingly enrolling in U.S community colleges as a starting point to their higher education. However, limited research examines the factors contributing to their successful transfer to a 4-year institution and bachelor degree attainment. Utilizing longitudinal transcript data from a large community college district in Texas, this study uses hierarchical logistical regression to compare college experiences and transfer outcomes based on region of origin. Findings demonstrate that while Sub-Saharan African students have a significantly higher probability of transfer than Asian and Latin American students, the majority of bachelor degree recipients were Asian students graduating in STEM fields. Delayed enrollment into college and academic preparedness in math were negatively associated with transfer for Latin American and Caribbean students.